Improving Student Learning Outcomes in Islamic Education Learning through the Method of Giving Learning Assignments and Recitations at Min 40 Pidie - Fitriana, Nana; Erlina (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aimed to improve students’ learning outcomes in the subject of Islamic Religious Education through the application of the Assignment and Recitation Method in Grade IV of MIN 40 Pidie, Peukan Baro District, Pidie Regency. The study employed a classroom action research design conducted in three cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 22 students, comprising 11 boys and 11 girls during the first semester of the 2025/2026 academic year. The results revealed that the implementation of the Assignment and Recitation Method significantly improved students’ learning achievement. The percentage of students achieving mastery increased from 68.18% in Cycle I to 77.27% in Cycle II, and reached 86.36% in Cycle III. The average score also rose from 69.09 in Cycle I to 76.36 in Cycle II, and 81.82 in Cycle III. This consistent improvement demonstrates that the Assignment and Recitation Method effectively fosters students’ responsibility, independence, and learning motivation. Therefore, this method can be regarded as an effective pedagogical approach for enhancing learning achievement and student engagement in Islamic Religious Education.